Correlating household second-hand smoke exposure and respiratory symptoms in school children - Matić, Branislava I; Vujanović, Dragana L; Dejanović, Snežana M; Jovanović, Verica S; Đonović, Nela Ž (PONS - medicinski časopis, 2017)
ABSTRACT Objective. Aim of this paper was to correlate exposure to household second-hand smoke and respiratory symptoms in participating school children attending ten primary schools in Belgrade, Serbia. Methods. A comparative cross-sectional study was conducted to determine the association between second-hand smoke exposure at home and respiratory symptoms in primary school pupils. The study was conducted in ten primary schools on 735 children, in 44 classrooms in Belgrade, Serbia. A standardized questionnaire was distributed to parents/care-givers, on child’s respiratory health, socioeconomic status and parents’ lifestyle habits, primarily cigarette smoking. Results. 78% of all exposed children have parents smoking up to 20 cigarettes/day, while more than 22% is exposed to parents´ household second-hand smoke of more than 21 cigarettes per day (p<0.0001). Respiratory disorders appear in 45.9% of children exposed to domestic second-hand smoke (CI 1.04-1.89), asthmatic symptoms in 33.5% (CI 0.94-1.78), while the least incidence of disorders is reported for continuous cough lasting for 3 months (3.3%, CI 0.44-2.36), wheezing after exercise (4.5%, CI 0.38-1.41) and being awaken by wheezing in last 12 months (7.4%, CI 0.89-3.28). Conclusion. Univariate logistic regression analysis proved exposure to parental smoking is a statistically significant predictor for the occurrence of respiratory symptoms in children. Keywords: household second-hand smoke, children, respiratory symptoms